REFOCUSING PENGELOLAAN APBD KABUPATEN SAROLANGUN DALAM PENANGANAN PANDEMI COVID-19 TAHUN 2020 - Aisyah Thasa Khairunnisa; Reni Dwi Purnomowati (Fakultas Hukum Universitas Trisakti, 2021)
Sarolangun in 2020 Number: 20.A/LHP/XVIII.JMB/5/2021 The government policy in refocusing the APBD aims to reduce the impact of weakening the community's economy and prevent the spread of the covid-19 virus, this policy is carried out by every local government, one of which is in Sarolangun Regency, Jambi Province in 2020. The formulation of the problem is whether the Refocusing of the APBD management of Sarolangun Regency, Jambi Province in 2020 is in accordance with Law Number 02 of 2020 concerning State policies and financial system stability for handling the covid 19 virus pandemic. (2) How is the responsibility for Refocusing the APBD management of Sarolangun Regency, Jambi Province during the covid 19 pandemic? This research method is juridical-normative, secondary data with primary data which is analyzed qualitatively and drawing conclusions with deductive logic. The results of the research, discussion and conclusions, first, the Sarolangun district government was constrained in refocusing the budget in the first stage due to a lack of understanding in adjusting the APBD so that there were warnings related to DAU delays, but in the second stage the Sarolangun district government had carried out the refocusing policy in accordance with applicable laws and regulations. Second, the Sarolangun district government is accountable for the management of the APBD, so that the use of funds from refocusing is outlined in the form of a District Government audit report.